IMPLIKASI STOCK SPLIT TERHADAP VOLUME PERDAGANGAN MELALUI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Awaluddin, Murtiadi; Alika, Nur Hikmah (Study of Scientific and Behavioral Management, 2023)
This study aims to determine the effect of stock split on Trading Volume through stock price in manufacturing companies listed on the Indonesian Stock Exchange in 2016-2021.This research is a type of quantitative research. Research using signalling theory.the population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. Determination of research samples based on purposive sampling method with a total sample of 13 companies. Research data is secondary data which is accessed through www.idx.co.id. Logistic regression analysis using path analysis test for stock split to Trading Volume through stock price. The results show that stock splits have a positive and significant effect on trading volume, stock splits have a positive and significant effect on stock prices have a positive and significant effect on Trading Volume, stock split have a positive and significant effect on stock prices, stock prices have a positive and significant effect on trading volume, and stock splits have an indirect effect on Trading Volume through stock price. Keyword : Stock Split, Trading Volume and Stock Price